The Cambridge handbook of classical liberal thought / edited by M. Todd Henderson. - Henderson, M. Todd (Cambridge University Press, 2018)
Polls suggest up to twenty percent of Americans describe their beliefs as 'libertarian', but libertarians are often derided as heartless Social Darwinists or naïve idealists. This illuminating handbook brings together scholars from a range of fields (from law to philosophy to politics to economics) and political perspectives (right, left, and center) to consider how classical liberal principles can help us understand and potentially address a variety of pressing social problems including immigration, climate change, the growth of the prison population, and a host of others. Anyone interested in political theory or practical law and politics will find this book an essential resource for understanding this major strand of American politics.